AL-QURAN TEACH THE IMPORTANCE OF TAKING CARE OF HEALTH PHYSICAL: Tafseer Surat Al-Baqarah - Guntur, Muhammad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
This thesis research using qualitative research through searching library data or library research. The method used in the discussion of the verse is the method of interpretation, which is used by the commentators in explaining the content of the verses of the Qur'an from various aspects by paying attention to the verses of the Qur'an as stated in the manuscripts. Starting with mentioning the verses to be interpreted, explaining the meaning of the lafaz contained in them, and explaining the contents of the verses. While the discussion method uses descriptive methods by collecting data, analyzing data and then drawing conclusions. Based on the results of the study, it shows that in the Qur'an letter al-Baqarah there are values ​​of physical education, including physical health education, environmental health education (hygiene), mental health education, and education on maintaining a diet.